1997
DOI: 10.1073/pnas.94.23.12568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in vivo adventitial expression of recombinant endothelial nitric oxide synthase gene in cerebral arteries

Abstract: Nitric oxide (NO), synthesized from Larginine by NO synthases (NOS), plays an essential role in the regulation of cerebrovascular tone. Adenoviral vectors have been widely used to transfer recombinant genes to different vascular beds. To determine whether the recombinant endothelial NOS (eNOS) gene can be delivered in vivo to the adventitia of cerebral arteries and functionally expressed, a replication-incompetent adenoviral vector encoding eNOS gene (AdCMVNOS) or ␤-galactosidase reporter gene (AdCMVLacZ) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
105
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(117 citation statements)
references
References 43 publications
12
105
0
Order By: Relevance
“…An animal model involving intact carotid artery was chosen as the focus for this study in the context of our ability to determine the effects of mechanical vector delivery in this tissue preparation morphologically, biochemically, and functionally, and because of our previous experience with vascular gene transfer in dogs 3,4,13,22,31 and rabbits. 19,20 Ex vivo experiments were carried out using arteries harvested from mongrel dogs.…”
Section: Animal Tissuementioning
confidence: 99%
See 4 more Smart Citations
“…An animal model involving intact carotid artery was chosen as the focus for this study in the context of our ability to determine the effects of mechanical vector delivery in this tissue preparation morphologically, biochemically, and functionally, and because of our previous experience with vascular gene transfer in dogs 3,4,13,22,31 and rabbits. 19,20 Ex vivo experiments were carried out using arteries harvested from mongrel dogs.…”
Section: Animal Tissuementioning
confidence: 99%
“…Experimental studies have demonstrated successful transfer of a variety of recombinant genes in the cardiovascular system both ex vivo and in vivo in animals and humans [1][2][3][4][5][6][7][8][9][10][11][12][13] suggesting that gene transfer technology may, in future, offer an effective therapeutic option for the spectrum of human cardiovascular diseases. [14][15][16][17][18] Most vascular gene transfer studies, to date, have utilized replication-incompetent adenovirus as a delivery vehicle for recombinant cDNA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations